2016
DOI: 10.1159/000444171
|View full text |Cite
|
Sign up to set email alerts
|

Practice of the Treatment of Milk Allergy in the UK: A National Audit

Abstract: Background: The management of cow's milk allergy (CMA) includes initial dairy exclusion with suitable dietary substitution, diagnostic challenges where indicated, and supervised re-introduction as the condition resolves. Information on clinician practice is limited. We audited the current practice of clinicians in the UK to evaluate adherence to international guidelines. Methods: An online questionnaire was sent to all clinicians whose practice included children identified on the national allergy society websi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In addition to the regional character, professionals who participate in scientific events can be assumed to be more concerned with their scientific knowledge and therefore do not accurately represent the universe of professionals. However, our results are generally similar to the results from other studies [17][18][19][20][21][22][23][24][25] that evaluated the knowledge and practices of health professionals. These studies [17][18][19][20][21][22][23][24][25] used procedures for recruiting interviewees that were similar or different to the procedure used herein.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the regional character, professionals who participate in scientific events can be assumed to be more concerned with their scientific knowledge and therefore do not accurately represent the universe of professionals. However, our results are generally similar to the results from other studies [17][18][19][20][21][22][23][24][25] that evaluated the knowledge and practices of health professionals. These studies [17][18][19][20][21][22][23][24][25] used procedures for recruiting interviewees that were similar or different to the procedure used herein.…”
Section: Discussionsupporting
confidence: 90%
“…During the period of exclusion of CMP, a nutritional status assessment should be performed by the health professional to establish the adequacy of food consumption for the child's nutritional needs [1,4,5,8] and family members must be oriented to perform a thorough reading of the labels of industrialized foods offered to their children [1,5,7,9]. Despite the existence of several guidelines [1,[4][5][6][7][10][11][12][13] for the diagnosis and treatment of CMPA, some surveys [6,7,[14][15][16][17][18][19][20][21][22] have shown that the practices and knowledge of health professionals are not fully in line with these recommendations. Few studies have investigated the knowledge and practices of pediatricians and nutritionists about CMPA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This can be performed as an open, single blind or double blind challenge, depending on clinical findings, history, and age of the child. However, there are conditions under which physicians may cancel a challenge procedure because either the diagnosis of CMPA is extremely high or the challenge procedure would be very risky if there is a history of anaphylaxis in a sensitized child (14) .…”
Section: Discussionmentioning
confidence: 99%
“…However, poor adherence to CMA guidelines has been reported in a number of studies. 8 Similarly, there is poor adherence to gastroesophageal reflux guidelines, the symptoms of which overlap with CMA. 9 Attention to all stages-from awareness of the guidelines through acceptance through applicability to adherence-is needed.…”
Section: Con P Os Iti Onmentioning
confidence: 99%